Green preparation of anti-inflammation an injectable 3D porous hydrogel for speeding up deep second-degree scald wound healing. Issue 59 (30th September 2020) - Xu, Xiao; Che, Lin; Xu, Lin; Huang, Doudou; Wu, Jiashen; Du, Zebang; Lin, Yuchun; Hu, Xiaoqian; Zhao, Qingliang; Lin, Zhongning; Xu, Ling
Abstract : The injectable 3D porous hydrogel with a double crosslinked network could be applied as a multifunctional injectable scald wound dressing material for anti-inflammation, necrotic tissue-removal, and wound closure. Abstract : Scalds are one of the most common injuries and the 4th cause of trauma globally. Alginate has emerged as a promising scald wound dressing. Herein, we present a facile applicable strategy for electron beam (EB) radiation crosslinking gelatin, alginate, and carboxymethyl cellulose (CMC) into an injectable three-dimensional (3D) porous hydrogel (3D-PH) with a double crosslinked network for reliable deep second-degree scald wound healing. In addition, the injectable 3D-PH stimulated proliferation and migration of dermal fibroblasts in vitro and the deep second-degree scald wound healing process is accelerated in vivo . Most importantly, in vitro results revealed that the injectable 3D-PH stimulated cell proliferation via inducing the expression of Ki-67, and suppressed inflammatory signals as indicated by the downregulation of inflammatory factors (IL-6, TNF-α) in L929 cells. We further demonstrated that the 3D-PGH accelerated the wound healing process of deep second-degree scald in vivo . This study indicated the injectable 3D-PH with a double crosslinked network could be applied as a multifunctional injectable scald wound dressing material for anti-inflammation, necrotic tissue-removal, and wound closure. These findings suggest that the injectable 3D-PH may be conducive to the evolution of new pharmaceuticals for burn wound healing.